Traditional Islamic boarding School Students’ Experience in Learning English through Reading based on Morphological Awareness Background: A Narrative Inquiry - Tama, Yudi Wili; Sulistyaningrum, Dyah; Mardiana, Rizdika (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2024)
Previous studies had shown that morphological awareness has an important role in the development of English ESP students' reading skills. However, there is still a gap in studies that specifically focus on the experiences of students in learning English through reading in various educational contexts, especially in traditional Islamic boarding schools. Therefore, this study aims to investigate (1) Students’ experience in learning English through reading in traditional Islamic boarding Schools, (2) the role of morphological awareness in learning to read, and (3) Impact of Morphological awareness on English reading ability. This research is a narrative inquiry study that aims to explore the experiences of three students from traditional Islamic boarding schools who took an English program where their morphological awareness background having an effect on learning English through reading. To collect data researchers use semi-structured interviews. Then, the data were analyzed using thematic analysis. The results of this study indicate that their morphological awareness plays an important role in their journey of learning English through reading, as indicated by their understanding of word forms, functions and structures. By integrating morphological awareness into language education, educators can enhance vocabulary development, improve reading comprehension, foster cross-linguistic transfer, and support language interrelations.